2020
DOI: 10.3390/d12040153
|View full text |Cite
|
Sign up to set email alerts
|

Coral Restoration Effectiveness: Multiregional Snapshots of the Long-Term Responses of Coral Assemblages to Restoration

Abstract: Coral restoration is rapidly becoming a mainstream strategic reef management response to address dramatic declines in coral cover worldwide. Restoration success can be defined as enhanced reef functions leading to improved ecosystem services, with multiple benefits at socio-ecological scales. However, there is often a mismatch between the objectives of coral restoration programs and the metrics used to assess their effectiveness. In particular, the scales of ecological benefits currently assessed are typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 52 publications
0
59
1
Order By: Relevance
“…A previous study in Indonesia by Ferse () reported that fish abundance and diversity increased most (up to 8‐fold) in restoration plots where hard coral cover was initially very low (below 5%) and where complexity was substantially increased (using artificial structures) from zero or one (zero or sparse vertical relief) to three (moderately complex). In this study that degree of change in complexity only occurred at Koh Tao (Hein et al ).…”
Section: Discussionmentioning
confidence: 64%
“…A previous study in Indonesia by Ferse () reported that fish abundance and diversity increased most (up to 8‐fold) in restoration plots where hard coral cover was initially very low (below 5%) and where complexity was substantially increased (using artificial structures) from zero or one (zero or sparse vertical relief) to three (moderately complex). In this study that degree of change in complexity only occurred at Koh Tao (Hein et al ).…”
Section: Discussionmentioning
confidence: 64%
“…Access to habitatspecific guidance at times of coral bleaching alerts may therefore begin to address conservation inequality, particularly if these efforts are coupled with effective local-scale mitigation, restoration, rehabilitation, conservation, and conservation strategies. [66][67][68][69] This would provide developing nations and areas with fewer resources access to the data and support needed to track and respond with greater specificity to bleaching risk and at a finer resolution than provided by current satellite alerts. As we enter an era of near-annual bleaching events it is increasingly evident that coral bleaching will continue to impact both coral reefs and coral reef users in profound and irrevocable ways.…”
Section: Future Outlookmentioning
confidence: 99%
“…Second, coral reef restoration has largely centered on corals only, neglecting many species which contribute to the biodiversity and functioning of reef systems ( Rinkevich, 2021 ). Third, a large range of methodologies defining success hinders its evaluation ( Boström-Einarsson et al, 2020 ; Hein et al, 2020 ). Lastly, restoration efforts often focus on the ecosystem itself rather than on the services provided by this ecosystems as for example local fisheries pose a challenge in densely populated regions with high dependence on these services ( White et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%